Immune Gene Expression and Locomotor Activity in Response to Vairimorpha ceranae Infection Across Five Honey Bee Subspecies - Cansu Özge Tozkar; Jay D. Evans (Insects)
This study evaluated immune gene expression and locomotor behavior across five Apis mellifera subspecies (Carniolan, Caucasian, Syrian, Muğla ecotype, and Yığılca ecotype) following controlled Vairimorpha ceranae infection. Six days post-infection, Caucasian, Carniolan, and Yığılca bees exhibited a significant upregulation of antimicrobial peptide (AMP) transcripts—hymenoptaecin, abaecin, defensin, and apidaecin—indicating a robust humoral response. Conversely, Syrian and Muğla bees showed weaker AMP expression and higher V. ceranae mRNA levels, indicating lower immunity and higher susceptibility. Positive correlations among AMP transcripts, especially in Caucasian, Carniolan, and Yığılca bees, suggested a coordinated response. Eater gene expression, critical for cellular immunity, decreased in infected Caucasian and Yığılca bees, coinciding with AMP upregulation. Vitellogenin expression, linked to immunity and longevity, increased in Carniolan and Syrian bees, correlating with higher early locomotor activity. Locomotor analysis revealed subspecies-specific behavioral responses. Syrian bees maintained the highest activity despite elevated V. ceranae mRNA and minimal AMP expression, suggesting unique resilience possibly mediated by vitellogenin. Muğla bees, despite high pathogen loads, exhibited decreased activity. Caucasian bees showed strong immune responses but reduced activity post-infection, reflecting potential physiological trade-offs. Overall, these findings underscore the role of genetic variability in shaping honey bee immune and behavioral responses to Vairimorpha and support subspecies-targeted breeding and disease management strategies to enhance resilience.